Effects of probiotics, prebiotics, and synbiotics on polycystic ovary syndrome: a systematic review and meta-analysis. Issue 4 (5th February 2023) - Li, Yuling; Tan, Yong; Xia, Guicheng; Shuai, Jiaqi
Abstract: This meta-analysis of randomized controlled trials (RCTs) was performed to summarize the effects of probiotics, prebiotics, and synbiotics on insulin resistance (IR), lipid profiles, anthropometric indices, and C-reactive protein (CRP) level for polycystic ovary syndrome (PCOS). We searched 8 databases from their inception until 1st October, 2020. The effect sizes were expressed as standardized mean difference (SMD) with 95% confidence intervals (95% CI). Subgroup analyses were undertaken for further identification of effects of probiotics, prebiotics, and synbiotics, based on the following aspects: (1) type of intervention (probiotics, prebiotics, or synbiotics); (2) study duration (≥ 12 weeks or < 12 weeks); (3) number of probiotic strains (multi strains or single strain); (4) probiotic dose (≥ 2 × 10 8 colony-forming units [CFU] or < 2 × 10 8 CFU). A total of 17 eligible RCTs with 1049 participants were included. Results showed that probiotic, prebiotic, and synbiotic intake decreased fasting plasma glucose (SMD, −1.35; 95% CI, −2.22 to −0.49; p = 0.002), fasting insulin (SMD, −0.68; 95% CI, −1.08 to −0.27; p = 0.001), homeostatic model of assessment for IR (SMD, −0.73; 95% CI, −1.15 to −0.31; p = 0.001), triglycerides (SMD, −0.85; 95% CI, −1.59 to −0.11; p = 0.024), total cholesterol (SMD, −1.09; 95% CI, −1.98 to −0.21; p = 0.015), low-density lipoprotein cholesterol (SMD, −0.84; 95% CI, −1.64 to −0.03; p = 0.041), very-low-density lipoprotein cholesterol (SMD, −0.44; 95% CI, −0.70 to −0.18; p = 0.001), and increased quantitative insulin sensitivity check index (SMD, 2.00; 95% CI, − 0.79 to 3.22; p = 0.001). However, probiotic, prebiotic, and synbiotic supplements did not affect anthropometric indices, high-density lipoprotein cholesterol, and CRP levels. Subgroup analysis showed that probiotic or prebiotic might be the optimal choice for ameliorating IR or lipid profiles, respectively. Additionally, the effect was positively related to courses and therapeutical dose. Overall, the meta-analysis demonstrates that probiotic, prebiotic, or synbiotic administration is an effective and safe intervention for modifying IR and lipid profiles.